2017
DOI: 10.3390/ma10091106
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Investigation of Heat-Treated Ultra-High Performance Concrete for Optimum Production

Abstract: Abstract:For optimum production of ultra-high performance concrete (UHPC), the material and microstructural properties of UHPC cured under various heat treatment (HT) conditions are studied. The effects of HT temperature and duration on the hydration reaction, microstructure, and mechanical properties of UHPC are investigated. Increasing HT temperature accelerates both cement hydration and pozzolanic reaction, but the latter is more significantly affected. This accelerated pozzolanic reaction in UHPC clearly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 28 publications
3
39
0
1
Order By: Relevance
“…The mechanical properties of HPEPC were written on the seventh day according to Table 3. The compressive strength after the 90°C heat treatment for 48 h can be regarded as a result of fully hydration reaction (Fehling et al 2014), and the compressive strength after the heat treatment tends to maintain their strength regardless additional curing duration (Kang et al 2017). For the same density and 40% EPS bulk ratio, the compressive strength of HPEPC was approximately eight times higher than that of EPS mortar.…”
Section: Mechanical and Thermal Properties Of Component Materials 32mentioning
confidence: 79%
“…The mechanical properties of HPEPC were written on the seventh day according to Table 3. The compressive strength after the 90°C heat treatment for 48 h can be regarded as a result of fully hydration reaction (Fehling et al 2014), and the compressive strength after the heat treatment tends to maintain their strength regardless additional curing duration (Kang et al 2017). For the same density and 40% EPS bulk ratio, the compressive strength of HPEPC was approximately eight times higher than that of EPS mortar.…”
Section: Mechanical and Thermal Properties Of Component Materials 32mentioning
confidence: 79%
“…Eine erhöhte Nachbehandlungstemperatur kann sowohl die Zementhydratation als auch die puzzolanische Reaktion beschleunigen, wobei der Einfluss auf Letztere von größerer Bedeutung ist . Dies führt zu einer Veränderung der Materialeigenschaften.…”
Section: Materialienunclassified
“…The increase of portlandite XRD peaks ( Figure 3) at temperature of 300°C means the heat treatment temperature up to 300°C promote portlandite formation through alite and belite hydration (Kang et al, 2017). Handoo, Agarwal and Agarwal (2002) examined morphology of portlandite by SEM and revealed that the morphology of portlandite after 200°C-heat treatment did not show any changes, but the portlandite crystals are deformed at 300°C and it was completely decomposed at 700°C (Handoo, Agarwal and Agarwal, 2002;Skantz, 2014).…”
Section: Figure 1 Ucs Test Apparatus and Its Samplementioning
confidence: 99%
“…Reaction of CaO with aluminum silicate is called as pozzolanic reaction. Higher temperature is effective in accelerating the pozzolanic reaction (Kang et al, 2017).…”
Section: Figure 1 Ucs Test Apparatus and Its Samplementioning
confidence: 99%